Developing the halal nutrition model - Abdul Latif, Mariam; Ab. Rahman, Suhaimi (Politeknik Negeri Padang, 2022)
Protecting the future population and the people’s welfare, as mentioned in the “Maqasid Shariah” or the aims of Islamic Law, is very important in view of the increasing negative behaviours existing in today’s societies at large. This research is aimed at studying on halal halal food consumed by the Prophet Muhammad s.a.w. and his eating practices which will impact any person’s health. Some foods mentioned in the Quran and Hadith were studied to associate the relationship of halal food and health. The method used is reviewing journals, the Qur’an and Hadith and conduct cross referencing. It is concluded that the Halal Nutrition Model is in line with the Malaysian Healthy Plate whereby it is actually suitable and befitting the halal nutrition but the whole model has to be without the haram elements which are blood, pork, carrion and liquor to provide proper nutrition guidelines for quality and better consumption of halal food for the future population.